The impact of ligands on the synthesis and application of metal halide perovskite nanocrystals. Issue 41 (18th October 2021) - Haydous, Fatima; Gardner, James M.; Cappel, Ute B.
Abstract : The surface ligation of metal halide perovskite nanocrystals (NC) influences the size/dimensionality, optoelectronic properties, chemical stability, and use of the NCs. Abstract : Metal halide perovskites have emerged as attractive materials for use in solar cells, light emitting diodes and other optoelectronic devices, mainly due to their impressive charge transport properties, strong light absorption, long carrier diffusion lengths and long excited state lifetime. The extensive research on these materials has paved the way for a new class of materials: metal halide perovskite nanocrystals (NCs). Due to their high photoluminescence quantum yield and narrow emission that can be tuned by size and compositional variations, perovskite NCs are considered to be ideal candidates compared to traditional quantum dots. With the growing interest in these materials and the current challenges in their commercialization, this review aims mainly to provide the necessary understanding of the influence of capping ligands on the synthesis and application of perovskite NCs. The different synthetic approaches and the role of ligands in determining the morphological and optical properties of the resulting NCs will be discussed. Thereafter, we review the advances in understanding the surface chemistry and ligation in the metal halide perovskite NCs. Lastly, we review the ligand exchange and management processes that are shown to be beneficial in improving the performance and stability of perovskite nanocrystal films for optoelectronic applications.